+0  
 
0
44
1
avatar

-3+2[5+9(-3+2)]

Guest Oct 27, 2017
Sort: 

1+0 Answers

 #1
avatar+237 
+1

We start with the parentheses.

-3+2=-1

-3+2[5+9(-1)]

Multiply 9*-1=-9

remove the parentheses

-3+2[5-9]

simplify the brackets

5-9=-4

2*-4=-8

remove the brackets

-3-8=-11

-11 is your answer

OfficialBubbleTanks  Oct 27, 2017

7 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details